Evaluation of octyl p-methoxycinnamate included in liposomes and cyclodextrins in anti-solar preparations: preparations, characterizations and in vitro penetration studies - de Souza de Bustamante Monteiro, Mariana Sato (Dove Medical Press, 2012)
PURPOSE: Awareness of the harmful effects of ultraviolet radiation has led to the increasing use of sunscreens, thus, the development of safe and effective antisolar preparations is important. The inclusion of sunscreen molecules in different release systems, like liposomes (lipo) and cyclodextrins (CD) is therefore required. METHODS: The in vivo sun protection factor (SPF), water resistance, and in vitro transdermal penetration test of octyl p-methoxycinnamate (OMC) in different dispersions, such as OMC encapsulated in liposomes (lipo/OMC), OMC encapsulated in β-cyclodextrins (β-CD/OMC), OMC encapsulated in both release systems (lipo/OMC and β-CD/OMC), and an OMC-free formulation were determined. RESULTS: Although the formulation containing only the lipo/OMC system revealed high value of in vivo SPF (11.0 ± 1.3) and water resistance (SPF = 10.3 ± 2.2), the formulation containing both release systems (lipo/OMC + β-cyclodextrin/OMC) showed the best result in the in vivo SPF test (11.6 ± 1.6). In the penetration test, the formulation containing the lipo/OMC system had better performance, since a high amount of OMC in the epidermis (18.04 ± 1.17 μg) and a low amount of OMC in the dermis (9.4 ± 2.36 μg) were observed. These results suggest that liposomes interact with the cells of the stratum corneum, promoting retention of OMC in this layer. CONCLUSION: According to our study, the lipo/OMC system is the most advantageous release system, due to its ability to both increase the amount of OMC in the epidermis and decrease the risk of percutaneous absorption.